THE INSERTION OF YOLANDA OREAMUNO IN THE COSTA RICAN “ELEGANT WORLD” (1931-1935) - Molina Jiménez, Iván (2019)
This article analyzes an aspect that has not been investigated about the renown Costa Rican writer Yolanda Oreamuno Unger (1916-1956): her insertion in the socalled elegant world of Costa Rica in the early 1930´s. Due to the premature death of her father (1917), Oreamuno underwent a social downgrading process, which she sought to overcome through three basic strategies: participating in various cultural activities, modeling for some of the leading painters of the time and competing in beauty contests. As a result of her efforts, she managed to become a national media figure and, for a short period of time, she frequented the most exclusive spaces of sociability of the wealthy families of San José.